91 SIMPLE, HIGHLY SENSITIVE CLINICAL PREDICTION SCORES FOR RULING OUT ESOPHAGEAL ADENOCARCINOMA IN PATIENTS WITH BARRETT'S ESOPHAGUS. (14th September 2020) - Chahal, D; Pi, S; Sharma, V; Duggan, S; Donnellan, F; Enns, R
Abstract:  : Barrett's Esophagus (BE) is a risk factor for development of Esophageal Adenocarcinoma (EAC). Detection of EAC at an earlier stage is known to improve patient outcomes, but only a very small proportion of patients with BE will progress to EAC. Even in the context of established risk factors, it is difficult to rule out EAC in patients with BE prior to or during endoscopy. Methods: We performed a retrospective chart review of all patients with non-dysplastic BE, dysplastic BE and EAC diagnosed at St. Paul's Hospital from 2012–2016 to investigate patient characteristics that would establish a risk score to discriminate patients with EAC from those without EAC. Results: 132 patients were identified. Patients with EAC had higher rate of smoking history (52.4% vs. 20.7%, p = 0.002), higher rate of prior malignancy (33.3% vs. 8.1%, p = 0.001), older mean age (71.0 +/− 8.3 vs. 61.3 +/− 12.2, p = 0.001), greater frequency of carcinoid malignancy (9.5% vs 0.0%, p = 0.024), greater incidence of family history of breast cancer (22.2% vs. 6.2%, p = 0.027) and lung cancer (23.5% vs. 4.1%, p = 0.004) and greater rate of endoscopic mucosal irregularity (85.7% vs. 28.8%, p < 0.001). A clinical risk score to discriminate between patients with EAC from those without EAC had an AUC of 0.90 and NPV of 0.97. Conclusion: We have devised clinical risk scores that could be used Risk scores, in combination with established factors such as degree of dysplasia, may help triage patients with BE appropriately with regards to timing of endoscopy. By ruling out EAC and in low risk patients, high risk patients might be monitored more carefully which could lead to earlier detection of EAC and improved patient outcomes.